Static and transient vacuolation in protein-based coacervates induced by charged amino acids - Zhenhua Li; Qing Liu; Han Ding; Zhuojun Meng; Qi-Hong Zhao; Nan-Nan Deng; Lifei Zheng (Nature Communications)
Abstract Vacuolation is a common phenomenon observed in many subcellular membrane-less organelles, such as paraspeckles, granules and nucleoli. Previous work suggests that such dynamic sub-structuration can be a result of charge disproportion at super-stoichiometric ratios of the assembling component. In this work, we demonstrate that other than remodeling the large coacervate-constituting components, the introduction of small charged motifs, amino acids, can also lead to the formation of static vacuoles in the coacervate droplets. Furthermore, we find that transient vacuolation can be induced when the charged amino acid (L-aspartic acid) is in situ produced in the coacervate droplets. The transient vacuoles can be tuned in lifetimes and initiated repeatedly, which highly resembles the ubiquitous dissipative assemblies in living systems that require a continuous supply of energy or matter. Therefore, our work may suggest an avenue to understand the sub-structuration within subcellular membrane-less organelles.